Heterotopic triplet gestation in natural conception following an IVF cycle: a rare case report - Mahapatro, Akshaya; Shankar, Kundavi; Varma, Thankam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Heterotopic gestation although common with assisted conception techniques is very rare with natural conception. High index of suspicion is required for timely intervention and prevention of morbidity and mortality. We report a rare case of heterotopic pregnancy in a 34 year of G2 P1 L2 women with previous conception following ART (IVF) for unexplained infertility. She presented with 7 ½ weeks of amenorrhoea with no other signs or symptoms and diagnosis picked up on ultrasound examination as triplet gestation at 7 weeks with twin intrauterine gestation with sac 1 - 19 × 5 mm with intrauterine live fetus, sac 2 - 17 × 7 mm gestational sac, no yolk sac or fetal pole imaged -anembryonic intrauterine pregnancy and sac -3 as right adnexal sac 5 × 6 mm - anembryonic right ectopic pregnancy. She was managed successfully with suction & evacuation & methotrexate.